Pediatric Sleep Tools: An Updated Literature Review - Sen, Tabitha; Spruyt, Karen (Frontiers in Psychiatry, 2020)
Since a thorough review by Spruyt et al. (2011), into the integral pitfalls of pediatric questionnaires in sleep, sleep researchers worldwide have further evaluated many existing tools. This systematic review aims to comprehensively evaluate and summarize the tools currently in circulation and provide recommendations for potential evolving avenues of pediatric sleep interest. 144 ‘Tool’-studies (70 tools) have been published aiming at investigating sleep in primarily 6-18 year olds per parental report. Although 27 new tools were discovered, most of the studies translated or evaluated the psychometric properties of existing tools. Some form of normative values have been established in 18 studies. More than half of the tools queried general sleep problems. Extra efforts in tool development is still needed for tools that assess children outside the 6-to-12 year-old age-range, as well as for tools examining sleep-related aspects beyond sleep problems/disorders. Especially assessing the validity of tools has been pursued vis-à-vis fulfilment of psychometric criteria. While the Spruyt et al. review provided a rigorous step-by-step guide into the development and validation of such tools, a pattern of steps continue to be overlooked. As these instruments are potentially valuable in assisting in the development of a clinical diagnosis into pediatric sleep pathologies, it is required that while they are primary subjective measures, they behave as objective measures. More tools for specific populations (e.g., in terms of ages, developmental disabilities, sleep pathologies) are still needed.